Measurement of potential absorption capacity in Colombia's innovative companies [Medición de la capacidad de absorción potencial en las empresas innovadoras de Colombia] (2017)
The article aims to evaluate the level of development of absorption capacity (RACAP) in Colombian SMEs. It is part of a sample of 363 Colombian SMEs (Dane, 2012), a literature review with the support of the content analysis and a linear regression model is used, which allow to show the existence of a positive linear correlation between the acquisition and the assimilation of external knowledge in the organizations under study. © 2017. revistaESPACIOS.com.